REPRESENTATION OF MORAL MESSAGES IN THE FILM HIGH & LOW THE MOVIE 3: FINAL MISSION (ROLAND BARTHES’ SEMIOTIC ANALYSIS) - Ardiansyah, Mohamad Rangga Rizky; Fikri, M. Andi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze how moral messages are represented in the film, focusing on how these meanings are constructed and conveyed through narrative and visual elements. Method: The research was conducted using a qualitative descriptive method by applying Roland Barthes’ semiotic approach, which includes three stages of analysis: denotation, connotation, and myth. Data were collected through observation of significant scenes in the film as well as documentation from various supporting literature. Results: The findings reveal that High & Low The Movie 3: Final Mission represents moral messages through the values of solidarity, courage, and sacrifice demonstrated in the actions of the main characters. The film deconstructs dominant myths related to power, development, and individual heroism, while constructing a new narrative about the collective strength of society in resisting injustice. Novelty: The urgency of this study lies in the lack of research employing Roland Barthes’ semiotics to analyze moral messages in High & Low The Movie 3: Final Mission. The conclusion of this study affirms that films can serve as an effective medium in delivering moral values and shaping social awareness. Future research is recommended to explore the representation of moral messages in other film genres or in digital-based visual media.